Assessing the Role of Women in Countering Radicalism: an Islamic Perspective - Hudzaifah Achmad Qotadah; Adang Darmawan Achmad (Khazanah Sosial, 2021)
Radicalism can lead to acts of terrorism that damaging feelings of safety and stability for many other entities and affecting all parts, whether soul, properties, and many more. In this research, the researcher uses a full qualitative method and documentation related to the topic of this research, which then will be analyzed descriptively. The main aim of this paper is to analyze the role of women based on the Islamic perspective regarding countering radicalism. The result found that another strategy to battle radicalism or spreading extremism is by the role and dedication of women in which women (mother) has become a landmark throughout family life to shape their children personality and mindset which enable them to remain mostly in the right direction as well as preventing radicalism and ideology that could turn to acts of violence.